Modifikasi Zeolit Dengan Tembaga (Cu) Dan Uji Sifat Katalitiknya Pada Reaksi Esterifikasi - Arjek, Orien Claudia Handayani; Fatimah, Is (Chemistry Department, Universitas Islam Indonesia, 2017)
Zeolite modification with Cu has been conducted. Material modification is done by impregnating Cu through a zeolite powder reflux process with CuSO4.5H2O solution so that theoretical Cu concentration is 5% followed by oxidation and reduction of solids. Material characterization was performed by x-ray diffraction analysis (XRD), Fourier Transform Infra-Red (FTIR) and acidity testing of Cu/Zeolite catalyst.The results showed that the crystallinity level of Cu/Zeolite did not change significantly when compared with natural zeolite. Changes occur at the intensity of the resulting peak, as at the peak of 2Î¸ 27.826 Âº which is the mordenite phase in Cu-zeolite has a peak intensity of 1360, while at zeolite with peak of 2Î¸ 27,760 Âº with the same phase meliki the smaller intensity of 1048. Testing the acidity of the catalyst was carried out by adsorbing pyridine into the catalyst, then calculating the adsorbed pyridine level, in the zeolite samples of pyridine adsorbed by 0.003 g / g while in the Cu-zeolite sample of 1.0574 g / g. The result of analysis with FTIR to show acidity level is seen in the range of wave number between 1450-1495 cm-1, from zeolite catalyst with wave number 1491,17 cm-1 peak intensity (% T) equal to 6,53, while at Cu-zeolite with wave number 1468.05 cm-1 peak intensity (% T) of 10.99. Testing of catalytic properties of Cu-zeolite catalyst on esterification reaction was done by taking acetic acid with concentration of 0.05 mol and methanol with concentration of 0.1 mol, then added 0.2 gram of catalyst, then reflux process for 1 hour. The results of reflux in the form of methyl esters were then analyzed by gas chromatography to see the retention time and the area of the resulting area. The use of Cu-zeolite catalysts yielding ester is indicated by the appearance of the ester peak.